EFISIENSI BIAYA PEMBANGUNAN PROYEK JALAN SP RESAK PETUNG PADA PT BANGUN CIPTA KONTRAKTOR - Adi Suroso, Ardian Catur Mujianto, LCA. Robin Jonathan (EKONOMIA, 2016)
Target of Research To know and analyse efficient or do not it him plan and realize the expense of in Development Of Project Walke Sp. Resak Petung at PT. Wake Up Creature Contractor. This Research is focussed by at activity of expenditure of and costs of progres work of field done by PT. Wake Up Creature Contractor Branch Kalimantan East.In this research of tester use Cost Estimate analyzer of is Expense Of ( RAB) Cost Estimate of is Expense of and Realization Budget. Activity Of Development of Project Walke early with planning and with good planning, to be got by its result of goodness also, in effort for the development of road;street project required by Cost Estimate of is Expense of ( RAB) able to determine furthermore step in development of road;street projectIf seen by Cost Estimate of is Expense of Development of project walke made by petung resak sp is year 2014 equal to Rp.57.538.528.763,54 in the reality disagree with Realization Budget year 2015 equal to Rp. 43.552.558.685,14 , and company get the rest of keutungan in the year 2015 equal to Rp.12.571.860.743,76.